From reverse transcription to human brain tumors - Dmitrenko, V.V.; Avdieiev, S.S.; Areshkov, P.O.; Balynska, O.V.; Bukreieva, T.V.; Stepanenko, A.A.; Chausovskii, T.I.; Kavsan, V.M. (Вiopolymers and Cell, 2013)
Reverse transcriptase from avian myeloblastosis virus (AMV) was the subject of the study, from which the investigations of the Department of biosynthesis of nucleic acids were started. Production of AMV in grams quantities and isolation of AMV reverse transcriptase were established in the laboratory during the seventies of the past century and this initiated research on the cDNA synthesis, cloning and investigation of the structure and functions of the eukaryotic genes. Structures of salmon insulin and insulin-like growth factor (IGF) family genes and their transcripts were determined during long-term investigations. Results of two modern techniques, microarray-based hybridization and SAGE, were used for the identification of the genes differentially expressed in astrocytic gliomas and human normal brain. Comparison of SAGE results on the genes overexpressed in glioblastoma with the results of microarray analysis revealed a limited number of common genes. 105 differentially expressed genes, common to both methods, can be included in the list of candidates for the molecular typing of glioblastoma. The first experiments on the classification of glioblastomas based on the data of the 20 genes expression were conducted by using of artificial neural network analysis. The results of these experiments showed that the expression profiles of these genes in 224 glioblastoma samples and 74 normal brain samples could be according to the Kohonen’s maps. The CHI3L1 and CHI3L2 genes of chitinase-like cartilage protein were revealed among the most overexpressed genes in glioblastoma, which could have prognostic and diagnostic potential. Results of in vitro experiments demonstrated that both proteins, CHI3L1 and CHI3L2, may initiate the phosphorylation of ERK1/ ERK2 and AKT kinases leading to the activation of MAPK/ERK1/2 and PI3K/AKT signaling cascades in human embryonic kidney 293 cells, human glioblastoma U87MG, and U373 cells. The new human cell line 293_CHI3L1, stably producing chitinase-like protein CHI3L1 was developed and these cells were found to have an accelerated growth rate and could undergo anchorage-independent growth in soft agar which is one of the most consistent indicators of oncogenic transformation. The formation of tumors in rats by 293_CHI3L1 cells evidences that CHI3L1 is an oncogene involved in tumorigenesis. In vitro experiments showed that constitutive expression of CHI3L1 gene promotes chromosome instability in 293 cells.